Stratigraphic sedimentary inversion using paths in graphs - Raymond, Alexandre Simões (2017)
The problem of Stratigraphic Sedimentary Inversion consists of analysing quantities of given sediments deposited in sampled regions of a depositional space and calculating the total volumes that are necessary to match the sampled data in a forward depositional simulation. This is a central problem in geology and oil exploration. Attempts to solve this problem were driven in the optics of optimisation techniques and trial-and-error approaches. We present a forward depositional simulation algorithm used in oil industries and a new counterpart inversion algorithm based on paths in graphs. It is conjectured that this algorithm can yield exact measurements when at least one feasible solution is available, instead of approximated solutions. We present a sample run of the algorithm in details. Results are discussed and future developments and extensions of this work are suggested.